1978
DOI: 10.3382/ps.0570735
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Feed Efficiency to Carcass Composition and Metabolic Rate in Laying Birds

Abstract: From a population of SCWL laying hens, 100 birds were classified according to their efficiency of conversion of feed to egg mass. From these, 4 "efficient" and 3 "inefficient" birds were used in energy metabolism studies involving indirect calorimetry, while the remainder were used for carcass analysis. Birds maintaining a criteria of 13.5-15.5 kg egg/48 weeks and classified as efficient or inefficient with respect to feed conversion had comparable body weight gains and did not differ significantly (P<.05) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 4 publications
(4 reference statements)
1
15
0
Order By: Relevance
“…There was also no indication of differences in feed waste between a cross from a commercial breeding programme and a cross with sires from a line which was selected over three generations for feed conversion rate. This is in agreement with the findings of Morrison and Leeson (1978) that feed waste did not influence variation of feed efficiency among individuals. Since feed waste can be substantially reduced through proper management (low feeding levels, choice of feeding system, choice of feed trough type, etc.…”
Section: Energy Loss By Feed Wastesupporting
confidence: 94%
See 3 more Smart Citations
“…There was also no indication of differences in feed waste between a cross from a commercial breeding programme and a cross with sires from a line which was selected over three generations for feed conversion rate. This is in agreement with the findings of Morrison and Leeson (1978) that feed waste did not influence variation of feed efficiency among individuals. Since feed waste can be substantially reduced through proper management (low feeding levels, choice of feeding system, choice of feed trough type, etc.…”
Section: Energy Loss By Feed Wastesupporting
confidence: 94%
“…Calculations based on their data suggest that at least 95% of the variance of ME/GE among individuals is determined by feed consumption. However, in a comparison of two groups of hens which were extremely different with respect to feed consumption but were similar in production and body weight, Morrison and Leeson (1978) found only a very small difference in metabolizability in the expected direction (12.6 as against 12.7 kJ g-' feed, i.e. 53% of the standard Genetic variafion and residual feed consumption: P. Luiting deviation among individuals).…”
Section: Energy Losses In Faeces and Urinementioning
confidence: 86%
See 2 more Smart Citations
“…Noblet et al (1993) reported that the increase in energy expenditure induced by the standing posture may be estimated as 27.3 kJ·min − 1 kg BW − 0.75 . In addition, the standing posture has been associated with RMEI (Morrisson and Leeson, 1978) who found that birds selected for high RMEI were standing more often than those selected for low RMEI. Several behaviour traits were graphically close to postures measured during the growing period and thus, explained the same variation in RMEI.…”
Section: Relationships Between Rmei and Behavioural Traitsmentioning
confidence: 96%